URGENSI NILAI AGAMA PADA MORAL ANAK DI ERA SOCIETY 5.0 - Madyawati, Lilis; Marhumah, Marhumah; Rafiq, Ahmad (UIR Press, 2021)
This study aims to identify and describe the importance of religious and moral values ​​instilled by parents in welcoming society in the 5.0 era. This research is qualitative with library research. A sorting method with two determining elements, children's spiritual and moral values, was used to analyze the data. Researchers explain the data into categories and characteristics. We also limited the data, performed content analysis, and studied the text literature. In the era of society 5.0: 1) parents are advised to educate their children as did Rasulullah (SAW); 2) parents are responsible for children's academic education; 3) parents are encouraged to grow the Rabbani generation (religion-based); 4) parents need to bring up good habits. Due to increasingly sophisticated technological developments, parents must increase their knowledge of this new technology, positively direct digital devices and media, and balance the time in using digital media and real-life interactions. In addition, parents are also encouraged to choose programs or applications that are positive for children that can positively impact their child's growth and development.